Pengaruh Karakter Debitur dan Pendapatan Nasabah terhadap Kolektibilitas pada Bmt Al-Muqrin - Sri Retnaning Sampurnaningsih (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of debtor character and customer income on collectibility at BMT Al-Muqrin. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study indicate that the debtor's character has a significant effect on collectibility by 43.4%, hypothesis testing is obtained t count > t table or (8.449 > 1.986). Customer income has a significant effect on collectibility by 49.3%, hypothesis testing is obtained t count > t table or (8,595 > 1,986). Debtor character and customer income simultaneously have a significant effect on collectibility with the regression equation Y = 13.633 + 0.338X1 + 0.526X2 and the contribution of the influence is 55.2%, hypothesis testing is obtained F count > F table or (56.629 > 2,700).